2015
DOI: 10.1177/0305735615596375
|View full text |Cite
|
Sign up to set email alerts
|

The effect of audio recording and playback on self-assessment among middle school instrumental music students

Abstract: This study examined the effect of audio recording and playback on middle school instrumentalists’ self-assessment. Middle school student musicians ( N = 112) completed a self-assessment immediately following their individual performance of an etude. The student musicians then listened to a recording of their individual performance and completed another identical self-assessment. A third identical self-assessment occurred 2 days later, again utilizing the recorded performance as subject material. The self-asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 63 publications
2
11
0
3
Order By: Relevance
“…The use of audio and video recordings, both in creating and viewing them, is also common, although the degree to which each of these activities is done remains unclear. Experimental studies have demonstrated their potential as tools to improve self-assessment (Johnston, 1993;Robinson, 1993;Daniel, 2001;Hewitt, 2002;Silveira and Gavin, 2016). Volioti and Williamon (2017) examined the use of audio recordings among instrumental learners, finding that students reported greater use of them than professionals, particularly for elements including goal setting and developing an interpretive style.…”
Section: Introductionmentioning
confidence: 99%
“…The use of audio and video recordings, both in creating and viewing them, is also common, although the degree to which each of these activities is done remains unclear. Experimental studies have demonstrated their potential as tools to improve self-assessment (Johnston, 1993;Robinson, 1993;Daniel, 2001;Hewitt, 2002;Silveira and Gavin, 2016). Volioti and Williamon (2017) examined the use of audio recordings among instrumental learners, finding that students reported greater use of them than professionals, particularly for elements including goal setting and developing an interpretive style.…”
Section: Introductionmentioning
confidence: 99%
“…Se esperaría que, el estudiantado ejerciera una autoevaluación continua de su práctica sobre la base de sus conocimientos y de estándares y criterios preestablecidos. Sin embargo, los estudios indican que gran cantidad de estudiantes podría no estar consciente de sus propios errores o fallas, hasta que se confrona con su propia ejecución (Daniel, 2001;Garrison, 2009Garrison, , 2010Silveira y Gavin, 2015). Dada la complejidad que una ejecución musical entraña, no es de sorprender que la mayoría de estudiantes no esté consciente de muchos de los errores que está cometiendo o ignore las carencias o debilidades de su ejecución, ya que esta involucra una gran variedad de factores que ocurren de manera simultánea en un breve periodo.…”
Section: A) La Audio-grabaciónunclassified
“…De acuerdo a diversos estudios empíricos, estas estrategias de práctica efectiva ayudan al estudiante a determinar si ha mejorado y a seleccionar la estrategia más adecuada para vencer los retos técnico-musicales (McPherson y McCormick, 1999;McPherson y Zimmerman, 2002;Nielsen, 1999;Rosenthal, Durairaj y Magann, 2009). Al mismo tiempo, agudiza el criterio de autoevaluación del estudiante (Daniel, 2001;Silveira y Gavin, 2015) y promueve la reflexión sobre el proceso de aprendizaje (Boucher, Dube y Creech, 2017). Para terminar, la ejecución instrumental frente a un compañero (evaluación de pares) contribuye al logro de mejores resultados, desarrolla la destreza para resolver problemas y facilita el entendimiento entre estudiantes (Sheldon, 2005).…”
Section: Marco Teóricounclassified
“…Sin embargo, no siempre es así. Las investigaciones coinciden en que la auto-evaluación sin un medio de contraste o comparación suele no reflejar la realidad total (Daniel, 2001;Boucher et ál., 2017;Bugos y High, 2009;Silveira y Gavin, 2015). Por el contrario, la revisión bibliográfica indica que la auto grabación en video y en audio, así como la asesoría y evaluación de pares representan estrategias de evaluación de alto nivel metacognitivo.…”
Section: Dimensión De Auto Re-direccionamientounclassified